Hubungan antara obesitas dan insiden kanker kolorektal di RSUP Sanglah tahun 2016-2017 - Anak Agung Sagung Mirah Trisuladara; Made Agus Dwianthara Sueta; Made Suka Adnyana (DiscoverSys Inc., 2019)
Introduction: Colorectal cancer is the third malignant disease in Indonesia. Obesity is one of the risk factors related to colorectal cancer. This research aims to role out relationships between obese and age to the incidence of colorectal cancer at Sanglah General Hospital.Method: Study design using case-control analytic model, covering 274 samples, divided into the group of colorectal cancer (137 persons) and non-cancer samples (137 persons). Secondary data were used for analysis obtained from medical records in year period of 2016-2017 at Sanglah General Hospital. Data were analyzed using Chi-square analysis and risk estimate model.Result: The result showed that the majority of colorectal cancer patients were male (53.3%), meanwhile for non-cancer patients were female (50.4%). The average age of colorectal cancer patients was 54 years old while 42 years for non-colorectal cancer patients. Based on the BMI groups, majority of cancer colorectal patients (62%) belongs to obese, while only 39.4% for non-colorectal cancer patients. Result of analysis showed that there is significant relationship between obese and the incidence of colorectal cancer (p value <0.001), with the risk increase of prevalence by 1.588 times higher for those patients with BMI â‰¥23.00 kg/m2 (95% CI 1.235-2.040). Result from the Chi-square test also indicated that there is significant relationship between age above 40 years and the incidence of colorectal cancer (p value <0.001).Conclusion: It can be concluded that there is significant relationships between obese and age above 40 years to the incidence of colorectal cancer.